Decatecholaminization of Septic Shock Patients in Intensive Care Unit: an Economic Assessment in the Italian Setting - Del Gaudio, Alfredo; Caiazza, Assunta; Bortone, Luana; Tomasso, Sonia; Bozzari, Ilaria; Vincenzi, Laura; Furneri, Gianluca; Tritapepe, Luigi (Farmeconomia. Health Economics and Therapeutic Pathways, 2024)
INTRODUCTION: Prolonged administration of norepinephrine to critically ill patients can lead to serious adverse events. In this context, the concept of “decatecholaminization” has emerged over the past decade, involving the association of vasopressin with norepinephrine to reduce catecholamines need. Additionally, beta-blockers can help prevent increased heart rate resulting from sepsis treatments. This study presents an economic analysis evaluating the economic implications of the decatecholaminization use in patients with septic shock treated in intensive care unit (ICU) from the Italian National Health Service (NHS) perspective. METHODS: Two analyses were conducted: (1) a patient-level comparison of costs between two real-world cases, one treated with decatecholaminization and one without this approach, and (2) a cohort-level analysis using a pharmacoeconomic model to project cost differences for the Italian National Health Service (NHS) before and after implementing decatecholaminization. RESULTS: In the patient-level analysis, the use of decatecholaminization results in increased pharmacological expenses (+€210), and cost reduction in resource utilization (-€30,412). Similarly, the cohort-level shows higher pharmacological costs (+€192 per patient) and lower cost for other resources (-€1,264 per patient) in the future vs current scenario, resulting in a cumulative cost reduction of -€1,072 per patient. Considering an eligible population of 39,207 patients, decatecholaminization results in a total cost reduction of approximately €42.4 million. CONCLUSION: This analysis supports the economic viability of decatecholaminization as an effective treatment for comprehensive management of septic shock. Further evaluation in real-world settings is needed to validate these findings and optimize clinical application.